Groundwater level under vacuum consolidation. Issue 2 (25th May 2021) - Chai, Jinchun; Lu, Yitian; Fu, Hongtao
Abstract : This study investigates the reduction of groundwater level in the soil deposit below the ground surface under vacuum consolidation. Theoretically, when the applied vacuum pressure is less than the air-entry value (AEV) of the soil deposit, the deposit will be in a saturated state and the groundwater level in the pre-fabricated vertical drains (PVDs) will not go below the ground surface during the vacuum consolidation process. In this case, the groundwater level is not a phreatic water level. If the applied vacuum pressure is larger than the AEV of the soil, part of the soil deposit can become unsaturated and the groundwater level in the PVDs can go below the ground surface. Further, the results of a large-scale vacuum consolidation model test using clay confirmed that during the consolidation process, the water level in the mini-PVD was always above the top surface of the model ground. Therefore, an attempt to measure the groundwater level in a vacuum consolidation area composed of clay deposits may not be worthwhile.